A nostoxanthin-producing bacterium, Sphingomonas nostoxanthinifaciens sp. nov., alleviates the salt stress of Arabidopsis seedlings by scavenging of reactive oxygen species - Jiang, Lingmin; Seo, Jiyoon; Peng, Yuxin; Jeon, Doeun; Lee, Ju Huck; Kim, Cha Young; Lee, Jiyoung (Frontiers in Microbiology, 2023)
A novel, nostoxanthin-producing, endophytic bacterium, designated as AK-PDB1-5T, was isolated from the needle-like leaves of the Korean fir (Abies koreana Wilson) collected from Mt. Halla in Jeju, South Korea. A 16S rRNA sequence comparison indicated that the closest phylogenetic neighbors were Sphingomonas crusticola MIMD3T (95.6%) and Sphingomonas jatrophae S5-249T (95.3%) of the family Sphingomonadaceae. Strain AK-PDB1-5T had a genome size of 4,298,284 bp with a 67.8% G+C content, and digital DNA-DNA hybridization and OrthoANI values with the most closely-related species of only 19.5 to 21% and 75.1 to 76.8%, respectively. Cells of the strain AK-PDB1-5T were Gram-negative, short rods, oxidase- and catalase-positive. Growth occurred at pH 5.0–9.0 (optimum pH 8.0) in the absence of NaCl at 4–37°C (optimum 25–30 °C). Strain AK-PDB1-5T contained C14:0 2OH, C16:0 and summed feature 8 as the major cellular fatty acids (>10%), while sphingoglycolipid, phosphatidylethanolamine, phosphatidylglycerol, phospholipids and lipids were found to be the major polar lipids. The strain was found to contain a yellow carotenoid pigment; natural products prediction via AntiSMASH tool found zeaxanthin biosynthesis clusters in the entire genome. Biophysical characterization by ultraviolet-visible absorption spectroscopy and ESI-MS studies confirmed the yellow pigment was nostoxanthin. In addition, strain AK-PDB1-5T was found significantly promote Arabidopsis seedling growth under salt conditions by reducing reactive oxygen species (ROS). Based on the polyphasic taxonomic analysis results, strain AK-PDB1-5T was determined to be a novel species in the genus Sphingomonas with the proposed name Sphingomonas nostoxanthinifaciens sp. nov. The type strain is AK-PDB1-5T (= KCTC 82822T = CCTCC AB 2021150T).